Open education find OER (by discipline) [electronic resource] (Virginia Polytechnic Institute and State University, 2017)
Quoted from the homepage: On these pages you will find textbook and non-textbook open educational resources. Discipline-specific pages are not intended to be exhaustive, but to showcase content that may be of interest to faculty considering adopting open educational resources for use in their classes. For more information about Creative Commons including license descriptions, please see the Creative Commons tab.